Proteasome expression and activity in cancer and cancer stem cells - Ioannis A Voutsadakis (Tumor Biology)
Proteasome is a multi-protein organelle that participates in cellular proteostasis by destroying damaged or short-lived proteins in an organized manner guided by the ubiquitination signal. By being in a central place in the cellular protein complement homeostasis, proteasome is involved in virtually all cell processes including decisions on cell survival or death, cell cycle, and differentiation. These processes are important also in cancer, and thus, the proteasome is an important regulator of carcinogenesis. Cancers include a variety of cells which, according to the cancer stem cell theory, descend from a small percentage of cancer stem cells, alternatively termed tumor-initiating cells. These cells constitute the subsets that have the ability to propagate the whole variety of cancer and repopulate tumors after cytostatic therapies. Proteasome plays a role in cellular processes in cancer stem cells, but it has been found to have a decreased function in them compared to the rest of cancer cells. This article will discuss the transcriptional regulation of proteasome sub-unit proteins in cancer and in particular cancer stem cells and the relationship of the proteasome with the pluripotency that is the defining characteristic of stem cells. Therapeutic opportunities that present from the understanding of the proteasome role will also be discussed.